Characterization of Potential Pathogenic Bacteria Isolated in High-Risk Infectious Services at the University Hospital Center of Suru-Léré in Benin - DEGBEY, Cyriaque; Quenum, Rosine Olga; Mousse, Wassiyath; SINA, HAZIZ; Socohou, Akim; BABA-MOUSSA, LAMINE SAÏD; hounsinou, Eric; BANKOLE, HONORÉ SOUROU (My University, 2021)
Healthcare-associated infections (HCAIs) remain a major public health concern. The aim of this study was to characterize potential pathogenic bacteria isolated in high-risk infectious services at the University Hospital Center of Suru-Léré in Benin. A cross-sectional, descriptive study was carried out on 215 samples with 8 air samples, 20 hand samples and 187 samples of medical-technical material. Genes for resistance to β-lactam antibiotics (blaTEM, blaSHV, blaCTX-M and blaOXA-1) were sought. The data were processed and analyzed using EPI Info version 3.5.4 software. A total of 10 bacterial species were identified. Of the 319 bacterial strains identified, Staphylococcus saprophyticus , Staphylococcus aureus and Enterococcus faecalis were predominant at 20.06%, 17.87% and 11.28% respectively. Antibiotic susceptibility showed that the majority of bacterial strains were multidrug-resistant. Of the 4 resistance genes sought, only the blaTEM and blaSHV genes were found. The poor microbiological quality observed in high-risk infectious services could be a risk factor for healthcare-associated infections. It is therefore useful to implement preventive measures in order to prevent or reduce the risk of healthcare-associated infections.
Keywords: Bacteria; Infection; Risk Factors; Benin